Struktura drzewostanów Tatrzańskiego Parku Narodowego – wyniki inwentaryzacji z lat 2016–2017 - Bodziarczyk, Jan; Gazda, Anna; Szewczyk, Janusz; Szwagrzyk, Jerzy; Zięba, Antoni; Zwijacz-Kozica, Tomasz (Leśne Prace Badawcze, 2019)
The composition and structure of forest stands in the Tatra National Park were examined using data gathered in 2016 and 2017 from 617 circular sample plots (0.05 ha each). The diameter at breast height of all living trees, standing dead trees, snags, and wind throws was measured along with diameters and lengths of fallen logs within the plot boundaries. Tree height was measured for all living trees within the core (0.01 ha) of the sample plots. Using the obtained data, height-diameter curves were calculated for all major tree species and in the case of spruce, the height-diameter relationships were also calculated separately for each of the three elevation zones (up to 1200 m, between 1200 and 1400 m, above 1400 m). For each elevation zone and park protection zone, we also determined the volumes of live and dead trees. The volume of living trees in the Tatra National Park amounted to 259 m 3 /ha, which was higher than the volume of dead trees (176 m 3 /ha). Snags constituted the largest part of the dead wood whilst over 97% of the standing dead trees were spruces Picea abies. Among living trees, the share of spruce ranged from 81% in the low elevation zone to 98% in the middle zone. Other significant species in the lower zone were Abies alba (11%) and Fagus sylvatica (4.5%), while in the middle and upper elevation zones only Sorbus aucuparia occurred in significant numbers. Furthermore, in the lower elevation zone, Fagus sylvatica was the only species displaying significantly higher volumes in the „strict protection” zone compared to the other park areas. In the „landscape protection” zone, Picea ab ies was the most dominant species and the share of other species in the lowest elevation zones calculated based on tree density was smaller than calculated based on tree volume, indicating problems with stand conversion from spruce monoculture to mixed forest.